2016
DOI: 10.1080/02652048.2016.1208296
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, statistical optimisation andin vitrocharacterisation of poly (3-hydroxybutyrate-co-3-hydroxyvalerate)/poly (lactic-co-glycolic acid) blend nanoparticles for prolonged delivery of teriparatide

Abstract: The purpose of this study was the preparation, optimisation and in vitro characterisation of PHBV and PLGA blend nanoparticles (NPs) for prolonged delivery of Teriparatide. Double emulsion solvent evaporation technique was employed for the fabrication of NPs. The nanoformulation was optimised using the Box-Behnken methodology. The morphological properties of NPs were assessed by both SEM and transmission electron microscopy (TEM). Encapsulation of Teriparatide within the NPs and lacking of chemical bonds betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…While the FT-IR analyses indicated great structural similarity between the 45S5 bioglass and BG groups, similar to the deconvolutions of the FTIR spectra in the study by Lee et al [ 77 ], who showed peaks associated with the structure of the bioglass, the BGT group was different, showing bands from the standard amide group (1660 cm −1 ) of the teriparatide drug molecule. This same band was observed in the study by Bahari Javan et al [ 79 ]. A decrease in the band of the group not bound to oxygen (NBO) can be observed; these bands are necessary for the dissolution of the bioglass, which will result in the formation of a layer of apatite hydroxycarbonate (HCA) on the surface of the material when in contact with fluids body or aqueous media.…”
Section: Discussionsupporting
confidence: 88%
“…While the FT-IR analyses indicated great structural similarity between the 45S5 bioglass and BG groups, similar to the deconvolutions of the FTIR spectra in the study by Lee et al [ 77 ], who showed peaks associated with the structure of the bioglass, the BGT group was different, showing bands from the standard amide group (1660 cm −1 ) of the teriparatide drug molecule. This same band was observed in the study by Bahari Javan et al [ 79 ]. A decrease in the band of the group not bound to oxygen (NBO) can be observed; these bands are necessary for the dissolution of the bioglass, which will result in the formation of a layer of apatite hydroxycarbonate (HCA) on the surface of the material when in contact with fluids body or aqueous media.…”
Section: Discussionsupporting
confidence: 88%
“…Drug release data were fitted into mathematical models of zero-order, first-order, Higuchi, and Korsmeyer–Peppas using the DD solver, an add-in of MS Excel, to build regression analysis of the mathematical expressions to explain the mechanism of drug release. …”
Section: Methodsmentioning
confidence: 99%
“…In g.1 (b), because of the Teriparatide present, a strong amide connection with the C = O group is located at 1492 cm -1 . The interaction between the N-H bending and the C-N stretching of the C-N-H group results in the 1435 cm -1 stretching bond [21].…”
Section: Study Of Chemical Bondingmentioning
confidence: 99%
“…However, other drugs have antiresorptive effects and prevent bone destruction. While the only FDA-approved anabolic drugs for the treatment of postmenopausal osteoporosis are Teriparatide (PTH ) and Abaloparatide, a PTHrP (parathyroid hormone-related protein), [14,15], Teriparatide is one of the systemic drugs whose disadvantages in using high doses are aggravated drug-induced side effects and the risk of osteosarcoma [16][17][18][19] and includes precautions for use in people with a history of kidney disease, hypercalcemia, and cardiovascular disease [20], and also the problems of intermittent use during the 2-year treatment period [21].…”
Section: Introductionmentioning
confidence: 99%